A population-based study on safety and health of drinking Litsea coreana tea (hawk tea) - Zhang, Han; Pu, Xiyu; Huang, Haijun; Huang, Qin; Yu, Bao; Cao, Weiguo; Zhang, Yong (Frontiers in Public Health, 2025)
BackgroundA herbal tea of leaves and stems of Litsea coreana, named Hawk tea locally, has been traditionally consumed in some places in southwestern China. However, there is no human based evidence about the safety and health effects of drinking hawk tea. This study aims to illustrate possible healthy effects of consuming hawk tea in a population with a habit of drinking hawk tea in Chongqing city.MethodsA hawk tea producing area located in Chongqing city was selected as the study setting, and residents were randomly designated. Self-designed questionnaires were administered to collect data, including basic information, the behaviors of consumption of hawk tea, and various health information.ResultsAmong the 4,363 respondents, 2,278 (52.2%) drank tea more 1 time per month and 957 (42.0%) were heavy drinkers. Among 2,278 Hawk tea drinkers, 62 reported various symptoms after drinking, and logistic regression showed no relationship between the symptoms reported and the characteristics of consumption (duration, frequency, and volume) (p > 0.05). In addition, heavy hawk tea drinkers had a lower risk of hyperlipidaemia than light hawk tea drinkers (p < 0.001, 95% odds ratio = 0.26).ConclusionWith the long history of consumption in the population and the effects on health as were shown in this study, hawk tea poses no detectable health risks to consumers and shows some benefit to metabolism of lipids. It can be recognized and recommended as a safe and healthy herbal beverage for people to consume in daily life. Further interventional studies on its safety and health benefits are warranted.